2008
DOI: 10.1038/sj.bmt.1705987
|View full text |Cite
|
Sign up to set email alerts
|

Serious acute or chronic graft-versus-host disease after hematopoietic cell transplantation: a comparison of myeloablative and nonmyeloablative conditioning regimens

Abstract: We previously reported a 25% incidence of serious graftversus-host disease (GVHD) (that is, acute or chronic GVHD that caused death, lengthy hospitalization or disability, or resulted in recurrent major infections) among 171 hematopoietic cell transplantation (HCT) recipients after nonmyeloablative (NMA) regimen. Here we present a retrospective study applying the same criteria to 264 recipients of peripheral blood HCT after myeloablative (MA) regimen, and compare the results with the previous study after addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These rates compare favorably with reported rates of chronic GVHD following RIC transplantation of 33% to 78%. [1][2][3][12][13][14][38][39][40][41][42][43][44][45] Addition of ATG in standard RIC regimens may be associated with a reduction in rates of chronic GVHD, however, not all investigators have confirmed this finding. 10,35,44,45 The relatively low rate of chronic GVHD we observed may result, in part, from the low rate of acute GVHD, as acute GVHD is a significant risk factor for development of chronic GVHD.…”
Section: Tli and Atg For Transplantmentioning
confidence: 81%
“…These rates compare favorably with reported rates of chronic GVHD following RIC transplantation of 33% to 78%. [1][2][3][12][13][14][38][39][40][41][42][43][44][45] Addition of ATG in standard RIC regimens may be associated with a reduction in rates of chronic GVHD, however, not all investigators have confirmed this finding. 10,35,44,45 The relatively low rate of chronic GVHD we observed may result, in part, from the low rate of acute GVHD, as acute GVHD is a significant risk factor for development of chronic GVHD.…”
Section: Tli and Atg For Transplantmentioning
confidence: 81%
“…All allogeneic transplant recipients received prophylaxis for acute GVHD depending on the type of donor and protocol in use at time of HCT and generally included either methotrexate or methotrexate and a calcineurin inhibitor [29–31]. Acute and chronic GVHD were diagnosed, graded, and treated as previously described [32–35]. Hepatitis C virus (HCV) screening began in 1991 as previously described [36].…”
Section: Methodsmentioning
confidence: 99%
“…This rate was comparable with what was observed in patients with a variety of hematologic malignancies who received the same nonmyeloablative HCT conditioning. 42 Long-term systemic therapy was needed to control GVHD over time, with 25% of current patients reported to still be on immunosuppression 7 years after allografting. In this study, we were not able to associate clinical GVHD with protection from relapse.…”
Section: Discussionmentioning
confidence: 99%